Synthesis of Banana-Shaped Liquid Crystals for Photoswitching Properties - Lutfor, M. R.; M. M., Yusoff; Hegde, Gurumurthy; Muhammad Nor Fazli, Abd Malek; Nurlin, Abu Samah; H. T., Srinivasa (Taylor & Francis, 2013)
Three banana-shaped monomers containing naphthalene as central units and azobenzene in side arms with terminal alkenes were synthesized and characterized. DSC, polarizing optical microscopy, and X-ray diffraction measurements prove that all compounds exhibit B6 phase. The trans-azobenzene showed high-intensity π–π∗ transition at about 365 nm and low-intensity n–π∗ transition at about 450 nm. The strong hotoisomerizationbehavior in solutions of the molecules displayed that trans to cis isomerization takes 45 sec whereas reverse process takes about 28 h and 30 min. This long thermal back relaxation is useful for creation of optical image storage.